2020
DOI: 10.1002/jbio.202000176
|View full text |Cite
|
Sign up to set email alerts
|

Safety and delivery efficiency of a photodynamic treatment of the lungs using indocyanine green and extracorporeal near infrared illumination

Abstract: Photodynamic inactivation (PDI) is a promising alternative for combating infections caused by antimicrobial resistant bacteria. Pneumonias are among the most worrisome infections because of their high-mortality rate. Previous studies have demonstrated the feasibility of using PDI with extracorporeal light to treat pneumonia. In this study, we analyzed key parameters for the viability of this treatment, including the selectivity of the photodynamic response for pathogens over host cells. Our results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Specifically, it was shown conditions in which ICG is deposited in the respiratory tract and activated with extracorporeal light without causing acute lung or liver damage. A follow-up study also showed that there is no evidence of the toxicity of the aPDT protocol in mammalian cell lines and mice in conditions that would completely inactivate bacteria [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was shown conditions in which ICG is deposited in the respiratory tract and activated with extracorporeal light without causing acute lung or liver damage. A follow-up study also showed that there is no evidence of the toxicity of the aPDT protocol in mammalian cell lines and mice in conditions that would completely inactivate bacteria [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an additional study demonstrated the selective of a PDI treatment using ICG and infrared light at 808 nm in vitro and the safety of aPDT in a murine model [28].…”
Section: Introductionmentioning
confidence: 99%
“…Experiment performed in triplicate on 3 different occasions (n = 9), mean value and standard deviation are shown. Source: KASSAB et al 92 The effect of different concentrations of ICG on a variety of bacterial strains and mammalian cell lines is shown in Figure 7. The presence of ICG is able to hinder the growth of S. aureus starting from 12.5 µM, decreasing the final CFU count in about 3 logs for Xen29.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment performed in triplicate on 3 different occasions (n = 9), mean value and standard deviation are shown. Source: KASSAB et al 92 Exposure to 808 nm infrared light alone did not cause death or inhibition to S. aureus strains nor to the lung cells lines (Figure 8). There was no statistically significant difference between groups for the bacteria.…”
Section: Light and Icg-pdi Toxicity On S Aureus And Pulmonary Host Cellsmentioning
confidence: 98%
See 1 more Smart Citation